2021
DOI: 10.3390/jcm11010214
|View full text |Cite
|
Sign up to set email alerts
|

Expectant Management of PPROM Improves Neonatal Outcome—A Retrospective Study of 562 Patients

Abstract: Prelabor preterm rupture of the membranes (PPROM) refers to the rupture of the membranes before 37 weeks, but also before the onset of labor. Approximately 3% of pregnancies are complicated by PPROM, which is an important cause of neonatal morbidity and mortality. The aim of the study is to demonstrate the benefit of expectant management in PPROM, compared to immediate birth, defined in our study as birth in the first 48 h. We analyzed 562 pregnancies with PPROM by gestational age groups and short-term morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In a retrospective Romanian study between October 2015 to November 2020, 3% of pregnancies between 24 + 0/7 and 36 + 6/7 gestation were complicated by PPROM, with a worse prognosis in premature infants compared to term infants [7]. This study showed a strong correlation between expectant management of PPROM and neonatal outcomes, thus, demonstrating the advantage of expectant management of PPROM over immediate birth within 48 hours of diagnosis.…”
Section: Literature Review and Comparison Of Epidemiological Studiesmentioning
confidence: 54%
See 3 more Smart Citations
“…In a retrospective Romanian study between October 2015 to November 2020, 3% of pregnancies between 24 + 0/7 and 36 + 6/7 gestation were complicated by PPROM, with a worse prognosis in premature infants compared to term infants [7]. This study showed a strong correlation between expectant management of PPROM and neonatal outcomes, thus, demonstrating the advantage of expectant management of PPROM over immediate birth within 48 hours of diagnosis.…”
Section: Literature Review and Comparison Of Epidemiological Studiesmentioning
confidence: 54%
“…This study showed a strong correlation between expectant management of PPROM and neonatal outcomes, thus, demonstrating the advantage of expectant management of PPROM over immediate birth within 48 hours of diagnosis. The limitation of the study was that the exact time between the ROM and presentation at the emergency could not be ascertained, as well as the lack of standard protocol and antibiotic resistance [7]. The index case was placed on bed rest for three days, following which operative cesarean delivery was done.…”
Section: Literature Review and Comparison Of Epidemiological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Preterm premature rupture of membranes (PPROM) is a condition in which the amniotic sac surrounding the fetus ruptures before the 37th week of pregnancy. [1][2][3] A diagnosis of PPROM carries the risk of various adverse maternal and neonatal outcomes, including premature birth, which can lead to complications for the newborn, such as respiratory distress syndrome, sepsis, and neurodevelopmental problems. 4,5 The risk of neonatal complications increases with earlier gestational age at delivery.…”
Section: Introductionmentioning
confidence: 99%